Inequality of opportunity in child health in Sudan: Across-region study - Ebaidalla Mahjoub Ebaidalla (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This study aims to examine the drivers of inequality of opportunity in health outcome among children below 5 years of age, using the Sudanese 2014 Multiple Indicator Cluster Survey. It investigates the variation in inequality across and within regions, decomposing inequality into a portion that is due to inequality of opportunity and a portion due to other factors, such as random variations in health. The results of the generalized entropy measures indicate that the overall inequality in child health is high, particularly in poor and conflict-affected regions. The contribution of inequality of opportunity to total inequality in child health outcome is found to be substantial and varies, both across and within regions. The results also reveal that the share of circumstances in inequality of opportunity in child health varies significantly according to health indicator and geographic region. Specifically, geographic location, parents' education, and parental wealth are found to be the principal factors contributing to inequality of opportunity in child health outcome.
Keywords: I12; I14; C15; D63; 330; child health; inequality of opportunity; Sudan